Improving antibiotic utilization in West Africa: enhancing interventions through systematic review and evidence synthesis - Eric S. Donkor; Abdul-Halim Osman; Bill Clinton Aglomasa; Aaron Awere-Duodu; Alex Odoom; Bismark Opoku-Asare; Gilbert Lazarus (Antimicrobial Resistance and Infection Control)
Abstract Background Bacterial infection has been estimated to become the leading cause of death by 2050, causing 10 million deaths across the globe due to the surge in antibiotic resistance. Despite western sub-Saharan Africa being identified as one of the major hotspots of antimicrobial resistance (AMR) with the highest mortality, a comprehensive regional analysis of the magnitude and key drivers of AMR due to human antibiotic use has not been conducted. Method We carried out a systematic review by conducting a comprehensive search in various databases including PubMed and Scopus for eligible articles published in the English Language between 1 January 2000 and 14 February 2024. Five key domains of antibiotic use were focused on: (1) antibiotic consumption; (2) appropriate antibiotic prescription; (3) indicators or key drivers of antibiotic use; (4) antimicrobial stewardship (AMS) interventions; (5) knowledge, attitudes and perceptions of antibiotic consumers and providers. Data were extracted from eligible papers for all the five domains under consideration and random-effects model meta-analysis was carried out for antibiotic consumption. Results Out of the 2613 records obtained, 64 articles which were unevenly distributed in the region were eligible for inclusion in our study. These articles reported on antibiotic consumption (5), appropriate antibiotic prescription (10), indicators or key drivers of antibiotic use (10), AMS interventions (10), and 31 studies reported on knowledge, attitudes and perceptions. Antibiotic consumption for inpatients has a pooled estimate of 620.03 defined daily dose (DDD) per 100 bed-days (confidence interval [CI] 0.00–1286.67; I2 = 100%) after accounting for outliers while prescribing appropriateness ranged from 2.5% to 93.0% with a pooled estimate of 50.09 ([CI: 22.21–77.92%], I2 = 99.4%). Amoxicillin, gentamicin, amoxicillin-clavulanate, metronidazole, and ceftriaxone were the commonly consumed antibiotics. Community-acquired infection, hospital-acquired infection, and prophylaxis were the major indicators of antibiotic use. AMS was effective to varying degrees with bundled interventions and gamified antimicrobial stewardship decision support application being the most effective. Healthcare workers demonstrated acceptable antibiotic knowledge but individuals from formal and informal settings self-medicate with antibiotics and had moderate to low knowledge of antibiotic use and resistance. Conclusion This review identified gaps in knowledge and highlighted areas where prompt actions are required, it further guides future research endeavors and policy development. The findings underscore the need for further implementation of AMS programs across the West African region to enhance understanding of antibiotic use patterns, prescribing practices, and the factors influencing them in the region.